Selected quasi-lexical and non-lexical units in Polish map task dialogues - KARPIŃSKI, Maciej (Archives of Acoustics, 2007)
The present study is focused on selected types of fillers, quasi-words and non-lexical words that are generally categorized as expressing positive or negative response in Polish task-oriented dialogues. Basic phonetic properties of such units are analyzed with a special focus on intonation. Some of their possible realizations are shown and some relations between their intonational form and meaning are hypothesized. A brief note on comparative background from our recent work is also provided and some implications for speech technology are mentioned.